Quantifying the Risk of Incompatible Kidney Transplantation: A Multicenter Study. Issue 7 (9th June 2014) - Orandi, B. J.; Garonzik‐Wang, J. M.; Massie, A. B.; Zachary, A. A.; Montgomery, J. R.; Van Arendonk, K. J.; Stegall, M. D.; Jordan, S. C.; Oberholzer, J.; Dunn, T. B.; Ratner, L. E.; Kapur, S.; et al.
<x xml:space="preserve">Abstract</x> Incompatible live donor kidney transplantation (ILDKT) offers a survival advantage over dialysis to patients with anti‐HLA donor‐specific antibody (DSA). Program‐specific reports (PSRs) fail to account for ILDKT, placing this practice at regulatory risk. We collected DSA data, categorized as positive Luminex, negative flow crossmatch (PLNF) (n = 185), positive flow, negative cytotoxic crossmatch (PFNC) (n = 536) or positive cytotoxic crossmatch (PCC) (n = 304), from 22 centers. We tested associations between DSA, graft loss and mortality after adjusting for PSR model factors, using 9669 compatible patients as a comparison. PLNF patients had similar graft loss; however, PFNC (adjusted hazard ratio [aHR] = 1.64, 95% confidence interval [CI]: 1.15–2.23, p = 0.007) and PCC (aHR = 5.01, 95% CI: 3.71–6.77, p < 0.001) were associated with increased graft loss in the first year. PLNF patients had similar mortality; however, PFNC (aHR = 2.04; 95% CI: 1.28–3.26; p = 0.003) and PCC (aHR = 4.59; 95% CI: 2.98–7.07; p < 0.001) were associated with increased mortality. We simulated Centers for Medicare & Medicaid Services flagging to examine ILDKT's effect on the risk of being flagged. Compared to equal‐quality centers performing no ILDKT, centers performing 5%, 10% or 20% PFNC had a 1.19‐, 1.33‐ and 1.73‐fold higher odds of being flagged. Centers performing 5%, 10% or 20% PCC had a 2.22‐, 4.09‐ and 10.72‐fold higher odds. Failure to account for ILDKT's increased risk places centers providing this life‐saving treatment in jeopardy of regulatory intervention.